Buddhism, Taoism, Confucianism and Shintoism: The Unpublished Writings of K. Satchidananda Murty - Vohra, Ashok (Taylor & Francis Group, 2023)
Cover -- Half Title -- Title Page -- Copyright Page -- Table of Contents -- Editors' Note -- Introduction -- Chapter 1 Nih.śreyasa Dharma: The Doctrine Leading to Salvation* -- Chapter 2 Attadīpo Bhava: Be a Lamp unto Yourself* -- Chapter 3 Buddhism: An Integrated Interpretation -- Chapter 4 Prajñāpāramitā: Perfect Wisdom -- Chapter 5 Buddhism and National Culture* -- Chapter 6 Andhra's Contribution to Buddhist Thought* -- Chapter 7 Buddhism-Taoism Coalescence under Confucian Auspices -- Chapter 8 Shinto: The Japanese Way of the Numinous -- Chapter 9 The Chinese Worldview -- Chapter 10 Major Asian Intellectual Traditions: Their Philosophy and Creativity* -- Index.